Self-assertion and its Relationship to Emotional Security Among Sample of Students From Damascus University (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research aims at present to detective level of Self-assertion  and Psychological Security among sample of research ,and  the correlation between Self-assertion  and its relationship to Psychological Security, as well as to detect differences between the average scores students at the scale Self-assertion  and Psychological Security among faculty members according to the following change (specialization of academic ) among the students of the Damascus university. To achieve this goal has been to use the following tools: Questionnaire to measure the of Psychological Security the preparation alawad,2013. And a questionnaire to measure of  Self-assertion  of the preparation of researcher. The study sample consists of (665) male and female students from Damascus university. The most important findings of Search: -Level of  Self-assertion  was Low. -Level of  Psychological Security was Low. -There are correlation statistically significant between the scores of students on a scale of Self-assertion and grades on a scale of Psychological Security. -There are differences between the mean scores of students on a scale of Self-assurance due to the variable specialization of academic favor theory colleges. -There aren't differences between the mean scores of students on a scale of Psychological Security due to the variable specialization of academic.